GANTI KERUGIAN PENGADAAN TANAH LRT JABODEBEK TERHADAP BANGUNAN PENGGARAP DI ATAS TANAH BUMN: Compensation For LRT Jabodebek Land Acquisition For Cultivator Buildings on BUMN-Owned Asset Land - Medianti, Innayah Rahmatunisa; Sihombing, Irene Eka (AMICUS CURIAE, 2024)
Land acquisition for the construction of the Jabodebek LRT Phase I needs to be considered about proper and fair compensation for those who are entitled. The main issues discussed are the mechanism for providing compensation to buildings on BUMN land assets affected by the Jabodebek LRT Phase I construction and how to resolve compensation for cultivator buildings whose ownership is still disputed over BUMN asset land. Regarding the compensation mechanism for land acquisition, it is regulated in Article 28-41 of Law No. 2 of 2012. In addition, the cultivator's building covering an area of ​​29 m2 could not be given directly because there was no agreement on the resolution of the ownership dispute. In conclusion, compensation was deposited at the local district court in accordance with Article 42 paragraph (2) letter b and settlement of compensation for the disputed cultivator's building with Decision Number 45/Pdt.G/2021/PN.Ckr. It should be given directly if there is a prior agreement to resolve the ownership dispute and the cultivator provides detailed proof of building ownership